Model of quality improvement and risk mitigation in the supply chain of concrete spun piles industry - Mahardhika, Welly; Iveline Anne Marie, .; Surjasa, Dadang; Mohd Yazid, Abu (AIP Publishing, 2024)
Pile foundations are construction parts made of wood, concrete and or steel, which are used to transmit surface loads to a lower surface level in the soil mass, these products are generally used in road projects (toll roads or national roads), wharves, airports and others. In the pile industry, product defects often occur, such as broken PC bars, cracks in stock, dry concrete, broken end plates and etc. These defect products can result in products not being able to become work in progress (WIP) or income for the company, WIP is divided into WIP 1 (products that are recognized by consumers) and WIP 2 (products that have not / are not recognized by consumers). In this study the intention was to design a pile product quality improvement and to mitigate activity risks in order to reduce the impact of product failure. Six Sigma DMAIC, namely Sub Model 1 Define, Sub Model 2 Measure, Sub Model 3 Analyze, Sub Model 4 Improvement and Sub Model 5 Control while the Risk Mitigation Model has 4 sub models that use the Risk Management approach, namely Sub Model 1 Risk Identification, Sub Model 2 Risk Analysis, Sub Model 3 Risk Evaluation and Sub Model 4 Risk Reduction.